The influence of future self-continuity on the willingness to engage in self-satisfied consumption: the mediating role of perceived economic mobility - Shi, Mingli; Fan, Chunlei; Tao, Ting; Gao, Wenbin (Frontiers in Psychology, 2026)
IntroductionWith the rise of emotional-value-driven consumption, self-satisfied consumption has become a significant market trend. However, research on its underlying psychological mechanisms remains limited. This study focuses on its future-oriented aspect, investigating how future self-continuity and perceived economic mobility influence the intention for self-satisfied consumption.MethodsA questionnaire-based study was conducted, collecting 388 valid responses nationwide. The concept of self-satisfied consumption was synthesized as healthy, rational, and autonomous consumption driven by self-development and personal pleasure. Data were analyzed using Hayes’ SPSS Process macro (Model 4) to test the proposed mediation model.Results(1) Both future self-continuity and perceived economic mobility positively predicted the intention for self-satisfied consumption. (2) Marital status was a significant demographic factor, with married individuals showing higher intention than unmarried ones. (3) Perceived economic mobility played a significant partial mediating role in the relationship between future self-continuity and consumption intention.DiscussionThe findings confirm that future-oriented psychological factors are key drivers of self-satisfied consumption, revealing a specific pathway through perceived economic mobility. This extends the theoretical understanding of the formation mechanisms of self-satisfied consumption and offers practical insights for consumer psychology and marketing strategies aimed at enhancing consumer well-being.